Analysis of 33kV Overhead Cable Fault Detection and Classification using MATLAB Software - Halim, Nurul Aliah Farisyah; Othman, Nordiana Azlin (Evolution in Electrical and Electronic Engineering, 2023)
Overhead transmission line protection is a crucial issue in power systems since overhead power lines are responsible for 85 to 87 percent of power system problems. Thus, fault detection techniques were created in response to this requirement to lessen the financial impact of fault situations and to make their correction simpler and more accurate. For transmission systems to operate more reliably and with fewer interruptions, accurate segment fault diagnosis is essential. By using a MATLAB-built model of a 33 kV small transmission line system, any faults in electrical overhead power lines are identified and analysed in this work. The system employs a modest transmission line system situated in a rural location. By measuring the transmission line system's phase current coefficient, the system may identify fault conditions. The designated power system model with the algorithm that calculates the precise detection and classification of transmission line faults was used for the analysis. With the implementation of four categories of faults that resulted in 11 types of faults as variables, this study examined the accuracy of data categorization and detection. The result shows the data collected as sinusoidal signals, and the threshold value is chosen to restrict the reading of the maximum coefficient for each phase's current under problematic circumstances based on the temporary overcurrent. A cutoff point of 200 A has been established for this project. As seen, the most significant coefficient for each phase current will exceed the threshold value in faulted situations. Using the data that had been collected, the system can pinpoint the different fault variables that affected the transmission line. The fault type that occurred on each phase of the current is successfully identified and classified by the system.